Rural entrepreneurship as an inclusive innovation strategy - Wong Copaja, Edgard Enrique (2023)
This article presents the analysis of indicators of inclusive innovation, on rural entrepreneurs in the Andean highlands of the Tacna region. The objective was to describe perceptions and conditions of inclusive innovation of rural entrepreneurs. There were limitations such as the dispersion of the population in the annexes of the high Andean areas, the users were not in one place, but in the mornings, they stopped in the field and in the afternoons at their homes, which has meant that the time of data collection is 6 months. The sample consisted of 253 people, determined by linguistic saturation, the sample consisted of profiles of people by function or sector of activity supported by the atlas ti program. In-depth semi-structured interviews were carried out with each of the people, these were carried out at home or at the workplace. Permission was requested to record the conversation in its entirety, the reactions, attitudes or gestures of the entrepreneur observed during the interview were incorporated. The perceptions and conditions of inclusive innovation of rural entrepreneurs have resulted in inclusive innovation leading to deepening in the benefits for the inhabitants and the local ecosystem, and the creation of added value that does not neglect nature, does not harm the environment and respects the customs of the Andean peoples.